Immune Aging and How It Works for Inflammation and Fibrosis - Nishiura, Hiroshi; Imasaka, Mai; Yamanegi, Koji; Fujimoto, Jiro; Ohmuraya, Masaki (Frontiers in Physiology, 2022)
Almost all mature cells that undergo apoptosis in an age-dependent or an accidental manner are completely recovered in tissue-specific microenvironments without any physiological changes. After peripheral blood leukocytes are released into the local region, fibroblast cells and new blood vessels commonly proliferate during wound healing. Inducible repair tools mainly supplied from blood vessels are cleared by peripheral blood phagocytic macrophages. Finally, hematopoietic stem cell (HSC)-derived precursor cells migrate from bone marrow (BM) to the microenvironment to rebuild damaged tissues (the mature immune system). In contrast to the mature immune system, the effects of aging on HSCs (long-term HSCs) and peripheral blood lymphocytes (long-term PBLs) are not clearly understood in the BM and thymus niches with tissue-specific microenvironments with some physiological changes (the aged BM niche) for incomplete rebuilding of damaged tissues (the aged immune system). In this review, the roles of the aged immune system in both a delay of acute inflammation and the development of chronic inflammation or fibrosis are discussed.